2016
DOI: 10.4103/2230-8210.172288
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of serum parathyroid hormone level in high-risk pregnancies as compared to nonpregnant control

Abstract: Objectives:To note the value of serum parathyroid hormone (PTH) levels in normal and high-risk pregnancies (HRP) in patients attending antenatal visits at All India Institute of Medical Sciences (AIIMS).Materials and Methods:This is a cross-sectional study where a total of 282 patients attending Gynecology Outpatient Department at AIIMS, New Delhi were recruited. Among the 282 subjects, 251 were pregnant, and 31 were controls. The serum was tested for serum PTH levels using Beckman coulter access 2 immunoassay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(30 reference statements)
2
1
1
Order By: Relevance
“…The findings of the present study were in contrast to the study done by Sharma et al 35 it was found that the serum PTH levels were significantly lower during pregnancy as compared to a nonpregnant state. It was found that there were no changes in serum PTH levels seen in high-risk pregnancies.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of the present study were in contrast to the study done by Sharma et al 35 it was found that the serum PTH levels were significantly lower during pregnancy as compared to a nonpregnant state. It was found that there were no changes in serum PTH levels seen in high-risk pregnancies.…”
Section: Discussioncontrasting
confidence: 99%
“…A lack of awareness of these changes in pregnancy may mask primary hyperparathyroidism or incorrectly diagnosis hypoparathyroidism. While previous studies have reported lower PTH levels [31][32][33] during pregnancy which is consistent with our findings, others have reported unchanged levels in comparison to the non-pregnant state. 34 Sepsis has been reported as the third most common cause of maternal mortality worldwide.…”
Section: Discussionsupporting
confidence: 93%
“…It is well established that parathyroid carcinoma is associated with significantly elevated preoperative PTH levels 23–25. However, as a normal physiological response to pregnancy, PTH levels decrease to the low-normal range (10%–30% of the non-pregnant value) during the first and second trimester and normalise by term26–28 while ionised calcium levels remain relatively constant throughout pregnancy 26. These physiological changes could account for the levels observed in our case.…”
Section: Discussionsupporting
confidence: 62%